2009
DOI: 10.1037/a0014760
|View full text |Cite
|
Sign up to set email alerts
|

Perceived income inadequacy as a predictor of psychological distress in Alzheimer's caregivers.

Abstract: The authors examined perceived income inadequacy as a predictor of self-reported depressive symptomatology and anxiety in the original sites of the Resources for Enhancing Alzheimer's Caregiver Health I project. Perceived income inadequacy, self-reported household income, and control factors (e.g., subjective health) were entered into hierarchical regression analyses predicting psychological distress. Findings suggest that perceived income inadequacy and not household income significantly predicted more self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 45 publications
(62 reference statements)
9
57
0
5
Order By: Relevance
“…As the financial difficulty of dementia caregivers has gained increasing attention from researchers, the results identify a significant effect of financial difficulty on depressive symptoms, providing support for the findings of previous studies (Lincoln 2007;Sun et al 2009) and extending the literature by providing a propensity score analysis to control for any selection bias caused by some imbalance in covariates between the group with financial difficulty and that without it.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…As the financial difficulty of dementia caregivers has gained increasing attention from researchers, the results identify a significant effect of financial difficulty on depressive symptoms, providing support for the findings of previous studies (Lincoln 2007;Sun et al 2009) and extending the literature by providing a propensity score analysis to control for any selection bias caused by some imbalance in covariates between the group with financial difficulty and that without it.…”
Section: Discussionsupporting
confidence: 67%
“…These four steps were conducted as follows. The check for the balance of covariates was performed through in the present study), Sun et al (2009) found a significant cross-sectional relationship between financial difficulty and depressive symptoms among dementia caregivers such that the greater the reported financial difficulty, the more likely the depressive symptoms. Lincoln (2007) examined older African-American caregivers and found a significant cross-sectional relationship between financial difficulty and depressive symptoms such that the greater the financial difficulty, the more likely the depressive symptoms.…”
Section: Propensity Score Analysismentioning
confidence: 98%
“…Caregiving often leads to additional costs such as medical expenses, lost wages, and employ ment benefits. Sun, Hilgeman, Durkin, Allen, and Burgio (2009) found that perceived financial strain had a stronger relationship with depressive symp toms and anxiety than actual income had with these outcomes among caregivers. Actual financial as sistance can also help relieve the financial burden associated with caregiving costs.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Moreover, studies have shown that caregivers' depressive symptoms are related to such factors as female gender (Hirst, 2003;Pirkis et al, 2010), perceived income inadequacy (Sun, Hilgeman, Durkin, Allen, & Burgio, 2009) and lack of social support (Malhotra, Malhotra, Ostbye, Matchar, & Chan, 2012). On the other hand, depressive symptoms seem to be reduced among caregivers who have greater self-efficacy (Romero-Moreno, Marquez-Gonzalez, Mausbach, & Losada, 2012) and among those with good family relationships (Francis, Bowman, Kypriotakis, & Rose, 2011).…”
Section: Introductionmentioning
confidence: 97%